Unmet Need in Non-muscle-invasive Bladder Cancer Failing Bacillus Calmette-Guérin Therapy: A Systematic Review and Cost-effectiveness Analyses from the International Bladder Cancer Group - D'Andrea, David; Mostafid, Hugh; Gontero, Paolo; Shariat, Shahrokh; Kamat, Ashish; Masson-Lecomte, Alexandra; Burger, Maximilian; Rouprêt, Morgan (European urology oncology, 2025)
BACKGROUND AND OBJECTIVE: Non-muscle-invasive bladder cancer (NMIBC) poses a significant clinical challenge, particularly when failing bacillus Calmette-Guérin (BCG) therapy, necessitating alternative treatments. Despite radical cystectomy being the recommended treatment, many patients are unfit or unwilling to undergo this invasive procedure, highlighting the need for effective bladder-sparing therapies. This review aims to summarize and report the evidence on the efficacy and to estimate the costs of bladder-preserving strategies used in NMIBC recurrence after failure of intravesical BCG therapy. METHODS: We systematically searched online databases for prospective studies investigating intravesical therapy, systemic therapy, or combination of both in patients treated previously with BCG. Owing to significant heterogeneity across the studies, a meta-analysis was inappropriate. A sensitivity analysis was performed in an exploratory manner. We used a decision-analytic Markov model to compare novel U.S. Food and Drug Administration-approved treatments with a 2-yr time horizon. KEY FINDINGS AND LIMITATIONS: A total of 57 studies published between 1998 and 2024, with 68 unique study arms and consisting of 2589 patients, were identified. The 3-mo overall response rate (ORR) across all studies, complete response rate (CRR) in concomitant carcinoma in situ (CIS) or CIS only disease, and recurrence-free rate (RFR) in papillary disease were estimated to be 52.4% (95% confidence interval [CI]: 45.4-59.2), 52.8% (95% CI: 42.9-62.6), and 26.4% (95% CI: 13.3-45.6), respectively. The 12-mo ORR, CRR, and RFR were estimated to be 78% (95% CI: 52.9-91.8), 27.8% (95% CI: 21.3-35.4), and 25.4% (95% CI: 18.2-34.2), respectively. The progression rate was estimated to be 13% (95% CI: 9-18.2). The mean proportion of patients treated with radical cystectomy was estimated to be 24.7 (range 0-85.7). The reported toxicity grades were overall mild, with a median of 3.4% (range 0-33.3%) participants experiencing a dose limiting toxicity. Compared with using radical cystectomy to treat patients failing BCG therapy, at a willingness-to-pay threshold of 100 000 USD, nadofaragene firadenovec was cost effective, with an incremental cost-effectiveness ratio (ICER) of 10 014 USD per quality-adjusted life year (QALY), while nogapendekin alfa inbakicept was less cost effective than nadofaragene firadenovec (ICER of 44 602 USD per QALY). Pembrolizumab, which dominated, was both less costly and more effective than the other strategies. CONCLUSIONS AND CLINICAL IMPLICATIONS: Salvage bladder-sparing therapies show a response rate of around 50% at 3 mo in patients with NMIBC failing BCG. However, long-term data are heterogeneous. Nevertheless, recently developed agents show promising tumor control activity. In the rapidly evolving landscape of urothelial cancer, some of these treatment strategies might be cost effective and improve patients' quality of life. The findings of our review highlight the need for novel, more effective therapeutic strategies. PATIENT SUMMARY: In this study, we reviewed the evidence on the efficacy of bladder-preserving strategies used in patients with bladder cancer recurrence after failing bacillus Calmette-Guérin (BCG) therapy. We found that these strategies show a response rate of around 50% at 3 mo. However, long-term data are heterogeneous. Nevertheless, recently developed agents show promising tumor control activity. In the rapidly evolving landscape of urothelial cancer, some of these treatment strategies might be cost effective and improve patients' quality of life.
Keywords: Non-Muscle Invasive Bladder Neoplasms; adjuvancia imunologická; nádory močového měchýře; analýza nákladů a výnosů; Neoplasm Recurrence, Local; invazivní růst nádoru; BCG vakcína; lokální recidiva nádoru; Treatment Failure; Humans; Cost-Benefit Analysis; nádory močového měchýře neinvadující svalovinu; Adjuvants, Immunologic; BCG Vaccine; Urinary Bladder Neoplasms; aplikace intravezikální; Administration, Intravesical; Neoplasm Invasiveness; lidé; neúspěšná terapie